2017
DOI: 10.1016/s2095-3119(16)61527-7
|View full text |Cite
|
Sign up to set email alerts
|

Manganese enhances the expression of the manganese superoxide dismutase in cultured primary chick embryonic myocardial cells

Abstract: In the present study, the effect of manganese (Mn) on antioxidant status and the expression of the manganese superoxide dismutase (MnSOD) gene in cultured primary myocardial cells collected from the chick embryos was investigated. The hypothesis that Mn supplementation would enhance the expression of MnSOD in cultured primary myocardial cells of chick embryos was tested. Eggs collected from Mn-depleted Arbor Acres laying breeder hens were incubated for 10 days and then myocardial cells were isolated and cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As a component of MnSOD, Mn can improve broiler’s antioxidant ability by catalyzing the reduction of superoxide anion to hydrogen peroxide [ 35 ]. An in vitro study indicated that MnSOD activity and mRNA expression level in chick embryonic myocardial cells were improved by 1.0 mmol/L of Mn as MnCl 2 treatment [ 36 ]. Studies also have shown that dietary inclusion of Mn as MnSO 4 , Mn methionine, or Mn oxide improved MnSOD, CAT, and GSH-Px activities and T-AOC, while reducing MDA level in serum, liver, and leg muscle of broilers [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a component of MnSOD, Mn can improve broiler’s antioxidant ability by catalyzing the reduction of superoxide anion to hydrogen peroxide [ 35 ]. An in vitro study indicated that MnSOD activity and mRNA expression level in chick embryonic myocardial cells were improved by 1.0 mmol/L of Mn as MnCl 2 treatment [ 36 ]. Studies also have shown that dietary inclusion of Mn as MnSO 4 , Mn methionine, or Mn oxide improved MnSOD, CAT, and GSH-Px activities and T-AOC, while reducing MDA level in serum, liver, and leg muscle of broilers [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then they were centrifuged for 4 min (12,000 × g , 4 °C), and the supernatants were subjected to western-blot analysis ( Zhang et al., 2017 ). The GAPDH protein was used to normalize the expression levels of SDH, CAT, COX or FTH protein ( Qin et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary antibodies and dilution rates were as follows: DMT1, bs-3577R, 1:500 (Bioss, Beijing, China); FPN1, bs-4906R, 1:500 (Bioss); and GAPDH, ab22555, 1:5,000 (Abcam, Cambridge, MA). The GAPDH protein was used to normalize the expression levels of the target protein ( Qin et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%